PENGARUH KUALITAS PRODUK, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Pembeli Produk Rotiboy di Mall Kota Semarang) - Noer Cahyo Santosa; Wahyu Hidayat (Universitas Diponegoro, 2019)
In this modern era, food and beverage businesses have rapidly been developing, especially for bakeries. Rotiboy is one of those bakeries which presents a very strong growth. A key to success in the business competitions is a company must produce and offer a product or service that meets their consumers’ needs. However, there are some of the essential factors that need our concern i.e., product quality, promotion, and location. This study aims to investigate the significant roles of product quality, promotion and location in purchase decisions (a study on consumers of Rotiboy at the Malls around Semarang). Unknown numbers of consumers of Rotiboy in Citraland and Paragon Mall were involved in the data collection. Meanwhile, a hundred thirty eight of which were taken as samples and analyzed using accidental and purposive sampling. The type of this research is Explanatory Research. The analysis used is a two-stage analysis using SPSS 17 software for Windows. Prior to data analysis, the author has undergone the validity test, reliability test, correlation coefficient, determination coefficient, simple and multiple regression analysis, and significance test (t-test and f-test). The result of this study indicates that product quality, promotion, and location have partially positive impacts on purchase decisions. Nonetheless, the variable that has the greatest positive impact is product quality. According to the findings, the author encourages Rotiboy’s constant innovations in terms of menu and taste to keep up with the competition, do some promotions that build good relationships with customers and relocate the stores to a more crowded and strategic place.